PERAN KEPALA SEKOLAH DALAM MENINGKATKAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP SULTAN AGUNG SEYEGAN SLEMAN - Hidayatullah; Tahajudin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
To improve the learning quality of Islamic Religious Education, the active role of school principals, especially at Sultan Agung Seyegan Middle School, Sleman Yogyakarta, will provide assistance to teachers in the learning process. This research focuses on the role of school principals in improving Islamic Religious Education at SMP Sultan Agung Seyegan Sleman Yogyakarta. Factors that support the improvement of the quality of Islamic religious education at SMP Sultan Agung Seyegan Sleman Yogyakarta are also the focus of this research. The principal's efforts to improve the quality of Islamic religious education at Sultan Agung Seyegan Middle School, Sleman, Yogyakarta, are also a major concern. In this study, a qualitative approach was used because solving problems will be easier when faced with reality and can interact directly with respondents. Based on this research, it was concluded that improving the quality of Islamic religious education at SMP Sultan Agung Seyegan Sleman was carried out by the principal through a program that was integrated with daily activities at school and carried out through routine activities. Several supporting factors in improving the quality of Islamic religious education at SMP Sultan Agung Seyegan Sleman include the existence of adequate infrastructure, such as a prayer room which is used for religious activities such as dhuha prayers and congregational prayers. In addition, a comfortable and conducive school environment is also an important supporting factor.